Exploring the conceptual relationship between e-skill, procedural and pedagogical content knowledge of teachers in the digital classroom environment - Adegbenro, Janet; Gumbo, Mishack T (South African Journal of Higher Education, 2016)
This paper reports on a study that was designed to formally explore the relationship between e-skills procedural, functional and pedagogical content knowledge of Business Studies teachers in the use of Information Communication Technology (ICT) infrastructure as pedagogical tools. We were specifically interested in the effective delivery of office data processing (ODP) teaching in the digital classroom environment at Further Education and Training (FET) colleges in Gauteng Province of South Africa. The demand for a highly skilled workforce to use ICT for innovation, creativity, improved performance and societal transformation is enormous and has led to it becoming known as e-skills. Based on the extended models of Mishra’s and Koheler’s TPACK-PrFPACK, a 65-item questionnaire using a 5-point scale was developed and used in this study, plus interviews and classroom observation. The population of this study was made up of 36 male and 41 female ODP teachers in eight Further Education and Training (FET) colleges. The findings revealed that procedural functional knowledge (PrF) has the highest direct impact on pedagogical knowledge. The findings also revealed that teacher experience is an important construct that moderates the dynamic relationship between e-skills, procedural and pedagogy.